Effects of Pluronic f68 Micellization on the Viability of Neuronal Cells in Culture - Arancibia-Miranda, N; Arancibia-Miranda, N (2013)
Triblock copolymers with surface-active properties, referred to as Pluronic, have shown potential medical applications such as drug delivery to selective targets in the human body. In particular, the transport of anti-inflammatory substances to the brain is required for illness treatment, thus the study of delivery agents that cross the blood-brain barrier is relevant. In this article we study the effects of the micelle formation on the morphologic and cytotoxic properties of Pluronic F68. We determinate the critical micellar concentration (CMC) by standard tensiometric and absorbance measurements, and also we analyze the morphology of polymers by atomic force microscopy. Our observations indicate that the morphological properties of F68 are drastically modified in the CMC range, as well as the ability to increase the viability of neuroblastoma cells maintained under culture conditions, as compared with nontreated cells. Our conclusions highlight the close correlation between morphological and physiochemical properties of Pluronic, which must be further understood in order to achieve highly controlled pharmacological uses. © 2013 Wiley Periodicals, Inc.